2013
DOI: 10.1021/jp3114623
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Effects on Emim[FeCl4], a Magnetic Ionic Liquid with Three-Dimensional Magnetic Ordering

Abstract: We report a combined study using magnetization and Raman spectroscopy on the magnetic ionic liquid 1-ethyl-3-methylimidazolium tetrachloroferrate, Emim[FeCl4]. This material shows a long-range antiferromagnetic ordering below the Néel temperature T(N) ≈ 3.8 K. The effects of pressure on the magnetic properties have been studied using a miniature piston-cylinder CuBe pressure cell. This three-dimensional ordering is strongly influenced when hydrostatic pressure is applied. It is observed that low applied pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 54 publications
1
42
1
Order By: Relevance
“…For Edimim[FeCl 4 ] they also lie antiparallel to each other along the c axis, while they are stacked identically one above the other in the a direction. 39 Fig. In the case of [Edimim] + units, the imidazole ring is aromatic and planar with all the rened values for the C-C and C-N bond lengths laying in the expected range of other imidazolium compounds.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…For Edimim[FeCl 4 ] they also lie antiparallel to each other along the c axis, while they are stacked identically one above the other in the a direction. 39 Fig. In the case of [Edimim] + units, the imidazole ring is aromatic and planar with all the rened values for the C-C and C-N bond lengths laying in the expected range of other imidazolium compounds.…”
Section: Resultsmentioning
confidence: 94%
“…The measured frequencies and their corresponding assignment in terms of the involved vibrational modes of the molecular ions are summarized in Table 4. 39,60 Variable temperature magnetic susceptibility measurements of the presented compounds were carried out on powdered samples in the 2-300 K temperature range. 6, black) belonging to the symmetry point group T d of the [FeCl 4 ] À iron complex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Other MIL systems have since been widely investigated. 1,[9][10][11][12] While ionic liquid systems with thermochromism related to changes in coordination of the metal centre have previously been reported, this has either been in the presence of additives or molecular solvents, or the magnetic properties were not investigated. [13][14][15][16][17] Here, we report on solutions of cobalt(II)isothiocyanate in thiocyanate ILs that show reversible switching of the cobalt(II) speciation from tetrahedral [Co(NCS)4] 2at room temperature to octahedral [Co(NCS)6] 4at temperatures around 233 K. These temperature-dependent changes in the co-ordination environment are accompanied by reversible changes in colour (blue to red) and by significant changes of the effective magnetic moment of these fluids.…”
Section: Temperature-dependent Switching Of Paramagnetism Of a Cobaltmentioning
confidence: 99%
“…So far, few studies have been conducted to understand the behavior of [emim]-based RTILs at high pressure [9,[11][12][13][14]. For example, Su et al [11] investigated the solid to liquid phase transition of 1-ethyl-3-methylimidazolium hexafluorophosphate ([emim][PF 6 ]) up to~1 GPa by high pressure differential thermal analysis and found that another crystalline phase exists between solid and liquid [emim][PF 6 ].…”
Section: Introductionmentioning
confidence: 99%